2004
DOI: 10.1111/j.0889-7204.2004.02305.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Frontier and Urban Elders With Chronic Heart Failure

Abstract: The purpose of this study was to compare 136 frontier and 148 urban patients with chronic heart failure who were aged 60 years and older. Medical records from 2000 to 2002 were reviewed from a regional tertiary hospital in Montana. While the two groups did not differ with respect to New York Heart Association functional class and number of comorbid conditions, the frontier sample was more likely to be male, married, and younger. Frontier patients were more depressed and scored significantly lower on quality-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Depending on geographic location, however, the majority of HF patients treated by a given facility may represent a distinctive population stratum with respect to ethnicity or socioeconomic status or both. Previous studies have shown that in patients with HF, ethnicity, socioeconomic status, and geographic location were associated with increased rates of hospitalization and rehospitalization, quality of life, and posthospitalization survival times 11–14 . Little is known, however, about the potential contribution of anemia to higher rates of morbidity and mortality in these patient subpopulations.…”
mentioning
confidence: 99%
“…Depending on geographic location, however, the majority of HF patients treated by a given facility may represent a distinctive population stratum with respect to ethnicity or socioeconomic status or both. Previous studies have shown that in patients with HF, ethnicity, socioeconomic status, and geographic location were associated with increased rates of hospitalization and rehospitalization, quality of life, and posthospitalization survival times 11–14 . Little is known, however, about the potential contribution of anemia to higher rates of morbidity and mortality in these patient subpopulations.…”
mentioning
confidence: 99%
“…Rural medical institutions also have limited technological and clinical resources and employ fewer cardiovascular specialists than urban hospitals (Casey et al, 2000, Bolin et al, 2011). Also, given the well documented association between hospital volume and quality of care, rural hospitals likely see a much lower volume of heart failure patients, and as a result could be less proficient at treating these patients than their urban counterparts (Wagnild et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to urban residents, patients in rural communities face greater challenges in managing their heart failure 10 . Difficulties include lack of local cardiac services and heart failure specialists 3 , 10 , lack of heart failure specific self-management guidance from providers 11 , 12 , less hospital discharge education at critical access hospitals, lack of follow-up by providers 13 , 14 , poor communication between the patient and providers, difficulty in traveling long distances for follow-up appointments and associated problems (time, fatigue, and cost) 11 , and feeling isolated and unsupported 15 , 16 . Despite these identified needs, effective programs to support heart failure patients in managing this complex, chronic condition in rural communities have not been reported 10 .…”
Section: Study Rationalementioning
confidence: 99%